IMPLEMENTASI LEARNING MANAJEMENT SYSTEM DALAM MENGELOLA UNIT KEGIATAN BELAJAR MANDIRI (UKBM) PADA KURIKULUM SISTEM KREDIT SEMESTER (SKS) DI SMA NEGERI MOJOAGUNG - Ahmad Ahmad; Fajar Indra Kurniawan (Menara Tebuireng, 2020)
The teaching model of Learning Management System is a software unit that is comprehensively integrated with various features for material delivery and management. By using LMS as an online learning medium, it can facilitate the interaction of teachers and students in the teaching and learning process and monitor the development of individual learning as expected by UKBM. UKBM has a wide influence and impact on education, especially teachers and students, in implementing the teacher's ability to manage learning using UKBM it requires a very good understanding so that the activities of each student in implementing and completing UKBM can be known with certainty. Teachers also have difficulty in measuring students’ independence in UKBM learning which subject teachers and school policy makers must know directly. Therefore, an information technology-based system is needed to solve these problems. One alternative is by the using of Learning Management System (LMS) at SMS Negeri Mojoagung.